Semiotic Analysis of Cartoon Content on the Instagram Account Feed of the President of the Republic of Indonesia @Jokowi - Rahman, Radif; Septariza, Dodi; Nazurah Setiawan, Filzah (Dinasti Research, 2024)
In the era of growing technological developments, the delivery of messages is not only done directly but can also be delivered indirectly through social media. Instagram social media is one of the places to communicate. This study aims to understand the signs and visual meaning of the cartoon content on the @jokowidodo account feed on January 1, 2024 which contains Happy New Year greetings using Ferdinand De Saussure's semiotic theory. The method used is a descriptive qualitative method with a constructivist / interpretative paradigm. The results of the study found that there are 25 contents in one